Effective writing : choices and conventions - Greenberg, Karen L. (United States of America : St. Martin´s Press, Inc., 1988)
This text centers around contemporany concerns in the teaching of composition: the acquisition of transferable skills, cognitive dissonance as an instrructional, and the development of values.
CONTENTS Preface PART I DRAFTING 1 Chapter 1 Exploring your thoughts and feelings about writing Chapter 2 Getting started Chapter 3 Shaping ideas Chapter 4 Writing paragraphs Chapter 5 Writing Essays PART II REVISING Chapter 6 Revising ideas and details Chapter Revising organization and improving coherence Chapter 8 Revising Sentence structure PART III EDITING Chapter 9 Editing sentence structure Chapter 10 Editing diction Chapter 11 Editing grammar and usage Chapter 12 Editing spelling and puntuation Part IV APPLYN YOUR WRITING SKILLS Chapter 13 Applying your writing skills APPENDIX Individualized Progress Logs
Incluye Contenido
Keywords: INGLÉS; ENGLISH LANGUAJE; WRITING; PARAGRAPHS; SENTENCE STRUCTURE